Phylogenetic homogenization of Amazonian tree assemblages in forest islands after 26 years of isolation. Issue 3 (13th August 2021) - Santo‐Silva, Edgar E.; Benchimol, Maíra; Peres, Carlos A.
Abstract: Question: Losses in species richness and functional diversity of tree assemblages have often been observed in Neotropical fragmented landscapes, but the way in which tree phylogenetic diversity responds to forest insularization over decadal timescales remains unclear. Here, we examine how tree phylogenetic diversity and structure have responded to profound landscape alteration and subsequent non‐random species losses within forest islands created within a vast hydroelectric reservoir. Location: Balbina Hydroelectric Dam Reservoir, Central Brazilian Amazonia. Methods: We used a large tree data set including 435 subplots of 0.05 ha each in 34 forest islands of variable sizes and three continuous forest sites in the Balbina Hydroelectric Dam, which contained 11, 000 stems representing 365 species and 188 genera. In each subplot we quantified tree phylogenetic diversity and structure and investigated their relationship with landscape structure metrics and the proportion of species within specific functional groups. Results: We uncovered a reduction in phylogenetic diversity in small (<10 ha) isolated islands, particularly in more fire‐prone areas near forest edges and surrounded by low amounts of forest cover. Additionally, assemblage‐wide phylogenetic decay was a result of non‐random species losses, given that tree assemblages dominated by small‐seeded, soft‐wooded pioneer species exhibited lower values of phylogenetic diversity and structure. We also uncovered a phylogenetic signal in traits associated with disturbance‐adapted species within this major man‐made forest archipelago. Conclusion: We uncovered pronounced phylogenetic diversity decay that was mostly driven by the proliferation of disturbance‐adapted species, such as small‐seeded pioneer species exhibiting fast life histories. Our results undermine more optimistic views based on studies in fragmented landscapes dominated by terrestrial matrix habitats, and indicate that true land‐bridge forest islands experience more detrimental effects on different components of tree diversity. Our study contributes to elucidate a growing underestimation of the pervasive threats posed by mega‐dams to tropical forest biodiversity and ecosystem functioning. Abstract : We investigate the phylogenetic diversity and structure of tree assemblages in 26‐years‐old Amazonian forest islands and uncovered a pattern of phylogenetic decay in small and isolated forest islands, mainly in those areas more fire‐prone and close to forest edges. This decay in phylogenetic diversity was driven by the proliferation of disturbance‐adapted species, such as pioneer species bearing small seeds.